A secreted LysM effector protects fungal hyphae through chitin-dependent homodimer polymerization. - Sánchez-Vallet, Andrea; Tian, Hui; Rodríguez-Moreno, Luis Gabriel; Valkenburg, Dirk-Jan; Saleem-Batcha, Raspudin; Wawra, Stephan; Kombrink, Anja; Verhage, Leonie; De Jonge, Ronnie; Van Esse, Peter; Zuccaro, Alga; Croll, Daniel; et al. (Public Library of Science, 2020)
Plants trigger immune responses upon recognition of fungal cell wall chitin, followed by the release of various antimicrobials, including chitinase enzymes that hydrolyze chitin. In turn, many fungal pathogens secrete LysM effectors that prevent chitin recognition by the host through scavenging of chitin oligomers. We previously showed that intrachain LysM dimerization of the Cladosporium fulvum effector Ecp6 confers an ultrahigh-affinity binding groove that competitively sequesters chitin oligomers from host immune receptors. Additionally, particular LysM effectors are found to protect fungal hyphae against chitinase hydrolysis during host colonization. However, the molecular basis for the protection of fungal cell walls against hydrolysis remained unclear. Here, we determined a crystal structure of the single LysM domain-containing effector Mg1LysM of the wheat pathogen Zymoseptoria tritici and reveal that Mg1LysM is involved in the formation of two kinds of dimers; a chitin-dependent dimer as well as a chitin-independent homodimer. In this manner, Mg1LysM gains the capacity to form a supramolecular structure by chitin-induced oligomerization of chitin-independent Mg1LysM homodimers, a property that confers protection to fungal cell walls against host chitinases. © 2020 Sánchez-Vallet et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Keywords: Inmunología vegetal; Quitina; Hongos patógenos; Fungal effectors; Chitin trigger immunity